POTENSI AGROINDUSTRI KOPI DI KAWASAN AGRO TECNO PARK (ATP) KABUPATEN TEMANGGUNG - Eny Hari Widowati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
Arabica coffee give a lot of contribution to the farmer household income, however the management of coffee is still subsistent, because farmers only sell coffee in the wet logs form to collectors. Average coffee Production in Temanggung Regency is 6.193,94 tons/year. There are agro industry of processing of dried and powder coffee at Tlahap Village, each of which is managed by a group of farmers however the implementation has not optimal developed. The aim of the research was to Analyze the type of agro industry that has potency to develop. The method of research is descriptive quantitative approach, location at Tlahap Village, Kledung Districts, Temanggung Regency, respondents were farmers, processors, traders and related agencies as 25 people. Data collection with interviews and FGD. Data analysis is used scoring techniques. The result showed that human resources in the Tlahap Village 65% in productive positions with average of land ownership were 1.32 ha/household. Scoring of results, indicators that have the highest value is the availability of land, availability of raw materials, the institutional culture. Ose dried coffee agroindustry that the potential to be developed is the type of coffee agro-ose dry with enough value to support. Agroindustrial roasted coffee and powder coffee has a value less support for development. conclusion: Ose dried coffee agro-industry can be developed by improving human resources through training, socialization and increasing production inputs and facilitation of equipment and partnerships.